Elaboración de piezas publicitarias para incentivar la realización de la prueba de detección del virus de inmunodeficiencia humana (VIH), y el síndrome de inmunodeficiencia adquirida (SIDA), a jóvenes ecuatorianos de 18 a 23 años. Caso: “Fundación Ecuatoriana Equidad” - Del Pozo Dueñas, Pablo Andrés (2019)
This project intention is the creation of advertising pieces to encourage young ecuadorians between ages of 18 to 23 who hace an active sex life, an HIV/AIDS test, an investigation and information gathering will be made, about the human inmunodeficiency virus (HIV) and also about the acquired inmunodeficiency syndrome (AIDS). What is sought with this research is ti know the basics abput the virus. know the stages of HIV infection, how and where people can be tested for the virus, in the same way, how treatment works to prevent HIV. Also, know what young people think avout this disease and the reason ther decide whether or not tot take the test. In the event that, they get tested, know their main motivation fot it. Finally, the purpose of generating these advertising pieces is to prevent young people AIDS, and to encourage them to get tested to know if they got the virus or just as a routine test.